PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA DI RUMAH SAKIT TEBET JAKARTA - Resa; Bonifasius M.H Nainggolan (Human Capital Development, 2023)
The purpose of this study was to determine the influence of leadership and work discipline on employee performance through work motivation at Tebet Jakarta Hospital. Collecting data by distributing questionnaires to employees. The sampling technique used quantitative methods with path analysis of 230 respondents. Data processing carried out in this study used the SmartPLS application version 3.2.9. The results of this study have a significant direct effect of leadership on work motivation, leadership has no positive and significant effect on employee performance, work discipline has a positive and significant effect on work motivation and work discipline has a significant positive effect on employee performance and for an indirect effect, leadership through work motivation significant effect on employee performance. In addition, work discipline through work motivation has a significant effect on employee performance.